Pengaruh Teknologi Informasi dan Komitmen Pelayanan terhadap Good Governance di Jajaran Pemerintah Kota Banda Aceh - Fanitra, Irma; Junaidi, Rahmad (Jurnal EMT KITA, 2020)
The main focus of this research is to analyze the effect of information technology and service commitment to the implementation of the principles of good government governance (GGG) and its impact on employee performance. The research was conducted at a number of the local government work unit (SKPD) within the Banda Aceh government. Collecting data through distributing questionnaires to 170 employees. Then the data were analyzed using multivariate statistics structural equation modeling. The study found a positive and significant effect of information technology and service commitment on GGG implementation and employee performance. The existence of GGG implementation not only has a positive impact on performance improvement, but also mediates the effect of information technology and service commitment on employee performance.Â Keywords: Employeeâ€™s performance, GGG implementation, information technology, services commitment, structural equation modelling.